HUBUNGAN PERILAKU MAKAN PERMEN DENGAN KARIES PADA SISWA SDN 1 DAWAN KALER KABUPATEN KLUNGKUNG TAHUN 2017 - Ida Ayu Dewi Kumala Ratih; Ni Luh Putu Sita Indra Dewi (Jurnal Kesehatan Gigi (Dental Health Journal), 2019)
About 90% of Indonesian children suffer from caries. School-age children are one group that is vulnerable to caries. Some things that have a close relationship with dental caries, both directly and indirectly include: oral hygiene, habit of consuming cariogenic food, depth of dental fissure, degree of acidity (pH) of saliva, and regularity of brushing teeth. Ni Luh Putu Sita Indra Dewi's research concluded that 65.78% of SD Negeri 1 Dawan Kaler students in Klungkung Regency in 2017 usually eat sweets every day. Most of the teeth affected by caries is 76.32%. The purpose of this study was to determine the relationship between candy eating behavior and caries in students at SDN 1 Dawan Kaler Klungkung Regency in 2017. This type of cross sectional study, uses secondary data from Ni Luh Putu Sita Indra Dewi research. The correlation test results obtained sig .: 0.108. Conclusion there is no relationship between the behavior of eating candy with caries in students at SDN 1 Dawan Kaler Klungkung Regency in 2017.